Computation of the expansion parameters of femto-waveguides using a two dimensional micro-Raman map and guided modes - Tejerina, Matías Rubén (2013)
The expansion parameters of a numerical elastic model that simulates femtosecond laser-material interactions are computed. To achieve this, two dimensional micro-Raman mapping, an elastic-optic finite element model,and the experimental intensity profile of the guided modes were used. To complement this data, the Raman deformation potential constants of the lithium niobate A1(TO4) phonon were obtained and compared with those reported in previous works.